2012
DOI: 10.4253/wjge.v4.i5.189
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management for small bowel enteroscopy in a World Gastroenterology Organization Endoscopy Training Center

Abstract: AIM:To study the anesthetic management of patients undergoing small bowel enteroscopy in the World Gastroenterology Organization (WGO) Endoscopy Training Center in Thailand. METHODS:Patients who underwent small bowel enteroscopy during the period of March 2005 to March 2011 in Siriraj Gastrointestinal Endoscopy Center were retrospectively analyzed. The patients' characteristics, pre-anesthetic problems, anesthetic techniques, anesthetic agents, anesthetic time, type and route of procedure and anesthesia-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…The combination use of a benzodiazepine and an opioid can profoundly drop blood pressure. Propofol has been shown to be safe and effective for sedation during endoscopic retrograde cholangiopancreatography, endoscopic ultrasonography and small bowel enteroscopy because these procedures require more time and patient co-operation [15][16][17][18][19] . Cardiovascular effects of propofol include decreases in cardiac output, systemic vascular resistance and arterial pressure.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination use of a benzodiazepine and an opioid can profoundly drop blood pressure. Propofol has been shown to be safe and effective for sedation during endoscopic retrograde cholangiopancreatography, endoscopic ultrasonography and small bowel enteroscopy because these procedures require more time and patient co-operation [15][16][17][18][19] . Cardiovascular effects of propofol include decreases in cardiac output, systemic vascular resistance and arterial pressure.…”
Section: Complicationsmentioning
confidence: 99%
“…Generally, GIE procedures can be performed by using topical anesthesia, intravenous sedation and general anesthesia [17,37,38] . Topical anesthesia and intravenous sedation techniques can be effectively done by non-anesthetic personnel.…”
Section: Prevention Of Sedation-related Complicationsmentioning
confidence: 99%
“…Adequate and effective sedation is important for the success and quality of endoscopic procedures, particularly in children . Nishimura et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the safety and efficacy of MAC in ERCP, endoscopic ultrasound (EUS), double-balloon enteroscopy (DBE), and some ophthalmologic and otolaryngologic operations [12][13][14][15][16][17]. Berkenstadt et al performed a craniotomy under MAC in 2001 [18].…”
Section: Introductionmentioning
confidence: 97%